2019
DOI: 10.1039/c9fo00599d
|View full text |Cite
|
Sign up to set email alerts
|

Glycated fish protein supplementation modulated gut microbiota composition and reduced inflammation but increased accumulation of advanced glycation end products in high-fat diet fed rats

Abstract: Glycated fish protein showed positively biological effects but increased AGEs accumulation in high-fat-diet-fed rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 43 publications
0
19
0
1
Order By: Relevance
“…Indeed, the food intake is comparable between WT and LKO as described in our previous publication [ 11 ], and thus the changes in fecal metabolites could be largely explained by gut microbial alterations, instead of food intake. LKO mice have significantly lower levels of fecal SCFAs than WT mice after a short-term HFD feeding, which could be explained by a reduction in SCFA-producing bacteria such as Rikenellaceae [ 33 ] and Ruminococcus_1 [ 41 ]. Our Spearman’s correlation analyses indicate that the fecal levels of all three SCFAs are negatively associated with body weight, supporting the conclusion that decreased abundance of SCFA-producing bacteria potentially contributes in part to the metabolic phenotype of LKO mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the food intake is comparable between WT and LKO as described in our previous publication [ 11 ], and thus the changes in fecal metabolites could be largely explained by gut microbial alterations, instead of food intake. LKO mice have significantly lower levels of fecal SCFAs than WT mice after a short-term HFD feeding, which could be explained by a reduction in SCFA-producing bacteria such as Rikenellaceae [ 33 ] and Ruminococcus_1 [ 41 ]. Our Spearman’s correlation analyses indicate that the fecal levels of all three SCFAs are negatively associated with body weight, supporting the conclusion that decreased abundance of SCFA-producing bacteria potentially contributes in part to the metabolic phenotype of LKO mice.…”
Section: Discussionmentioning
confidence: 99%
“…From our correlation analyses, the expansion of Dubosiella and Angelakisella has a positive correlation with body weight but a negative correlation with fecal SCFAs, suggesting that these bacteria have a novel role in obesity-related microbial dysbiosis. Moreover, Lcn2 deficiency inhibits the growth of SCFA-producing bacteria such as Rikenellaceae [ 33 ] and Ruminococcus_1 [ 41 ]. All of the above-mentioned changes in gut microbiota could be linked to the decreased levels of fecal SCFAs in LKO mice and explain part of the mechanisms for the metabolic phenotype of LKO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Further metabolomic analysis revealed alterations in pathways related with carbohydrate and amino acid metabolism (Qu et al., 2018). By contrast, when high‐fat diet‐fed rats were exposed to a highly glycated fish protein, diminished populations of the genera Helicobacter and Lachnospiraceae_NK4A136_group were noticed (Mao et al., 2019). With respect to human observations, information on the dAGEs‐microbe interaction is limited.…”
Section: Health Implications Of Dages: Perspectives To Fill the Gap Bmentioning
confidence: 99%
“…This may be related to the Maillard reaction of proteins in the formation of preserved egg. It was also reported that the intake of glycated fish protein could reduce the level of Proteobacteria in the intestinal flora . Moreover, Proteobacteria are gram‐negative bacteria; a higher level of Proteobacteria in the DEW group therefore leads to a higher amount of LPS in the intestine compared with the PEW group …”
Section: Discussionmentioning
confidence: 96%